*Mechanisms of circular RNA in drug resistance of lung cancer: therapeutic targets, biomarkers, and future research directions - Xuanlin Tao; Xixian Ke; Gang Xu (Discover Oncology)
Abstract Lung cancer is one of the most prevalent malignant tumors globally, posing significant challenges to treatment outcomes. Circular RNAs (circRNAs), a novel class of non-coding RNAs, have emerged as crucial regulators in cancer biology, influencing drug resistance, progression, and prognosis. Due to their closed-loop structure, circRNAs demonstrate high stability and resistance to degradation, making them promising diagnostic and therapeutic targets. Here we summarize the mechanisms by which circRNAs mediate drug resistance in lung cancer, focusing on their roles in chemotherapy, targeted therapies, and immunotherapy. We highlight how circRNAs interact with microRNAs (miRNAs) and proteins to regulate signaling pathways and alter drug sensitivity. Additionally, circRNA expression patterns hold potential as biomarkers for predicting treatment response. By synthesizing the latest research, we offer new insights into circRNA functions and suggest future directions for overcoming drug resistance in lung cancer. Graphical Abstract